IMPROVING STUDENTS' READING SKILL THROUGH COLLABORATIVE LEARNING - Arliani Gunawan Putri; Arrin Nur Octavialis; Irma Savitri Sadikin (PROJECT (Professional Journal of English Education), 2019)
Abstract This research aims is to find out how effective students’ reading skill after they were instructed by using Collaborative Learning. Sample of the research was 36 students in 7th grade of SMPN 5 Cimahi. The researcher administered reading test in collecting the data. The result of the data analysis showed that there was a significant improvement in students’ reading skill after learning through Collaborative Learning. It could be seen from students’ average score in pretest was 64,81 and students’ average score in posttest was 75,56. In short, Collaborative Learning could enhance students’ reading skill.Keywords: Collaborative Learning, Improving, Reading Skills